The Effect of Acid Sanitizers on the Microbiome of Re-use Water - Feye, Kristina M.; Micchichi, Andrew C.; Rubinelli, Peter M.; Knueven, Carl J.; Thompson, Dale R.; Kogut, Michael H.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2020)
Due to global climate change, water is becoming increasingly scarce. The poultry industry is a major consumer of fresh water; therefore, in order to reduce their environmental footprint, companies are in the beginning stages of evaluating water for re-use. Re-use water is classified as water from the poultry plant that has been collected, sanitized, and used again during poultry processing. Necessarily, this water must be potable as it otherwise produces a significant risk to the poultry industry. One of the most commonly used sanitizers in processing water is peracetic acid (PAA). At high concentrations, PAA is corrosive to the metal equipment in the plant and introduces a significant occupational hazard to plant workers. Inorganic sanitizers, such as sodium bisulfate (SBS), have documented antimicrobial and sanitation effects on a variety of surfaces. In this study, SBS and PAA were compared for their ability to sanitize re-use water collected from a local poultry plant. Fresh, commercial poultry processing plant re-use water was collected at the end of a processing shift and used within 1 h of the collection. Microcosms were created to simulate the sanitation environment and a time course collection of live microorganisms were collected and evaluated for aerobic plate counts, total Enterobacteriaceae, and Salmonella load. The microcosms contained either SBS (1, 2, or 3%) or 200 ppm PAA throughout the course of the study. Water samples were collected at 0, 15, 30, and 60 min post-sanitation. The water was evaluated for total Enterobacteriaceae and microbial load using traditional plating methods and the total DNA was extracted and sequenced using the 16S rDNA Illumina MiSeq v3 Platform targeting the V4 region of the prokaryote rDNA molecule. All sanitation methods resulted in nearly undetectable XLD and APC counts by 60 m (P < 0.05), with 1 and 2% SBS having a slight rebounding of APC counts by 60 m. The sequences were analyzed using the QIIME2.2018.08 pipeline. Changes in alpha diversity and beta diversity were indicated across time and by treatment group, which may reflect the cumulative effects of the sanitation treatment (killing, delayed killing, and the emergence of resistant populations). Overall, based on the ANCOM results, SBS groups had less Pseudmonas and more Bacteroides while PAA groups had greater Actiobacter and Gallinobacterium (Q < 0.05). The results of this study indicate that SBS is as efficacious as PAA for decreasing bacterial loads in poultry re-use water, but it may favor different populations of bacteria in that water. Therefore, while more studies are needed to evaluate the changes in the microbiome when re-use water is applied to carcasses, evidence presented herein suggest that the choice of sanitizer in water re-use sanitation may impact downstream microbial loads.